Periodontal disease and osteoporosis association and mechanisms: A review of the literature - Marcelo R. Marques; Marco A.D Silva; Silvana P. Barros (Universidade Estadual de Campinas, 2015)
Periodontitis and osteoporosis, diseases that affect millions of people in world, present bone loss as common hallmark. Prevalence of both osteoporosis and tooth loss increase with advancing age in both women and men. Systemic bone loss has been proposed as a risk factor for periodontal disease with increasing evidences that osteoporosis, and the underlying loss of bone mass characteristic of this disease, is associated with periodontal disease and tooth loss. Periodontitis has long been defined as an infection-mediated destruction of the alveolar bone and soft tissue attachment to the tooth, responsible for most tooth loss in adult populations. Current evidences including several prospective studies support an association of osteoporosis with the onset and progression of periodontal disease in humans. Systemic loss of bone density in osteoporosis, including that of the jaw, may provide a host system that is increasingly susceptible to infectious destruction of periodontal tissue. Studies have provided evidence that hormones, heredity, and other host factors influence periodontal disease's incidence and severity. This paper reviews the role of estrogen deficiency and osteoporosis in oral bone healthy and the current evidences on the association between periodontal disease and osteoporosis.